Millimeter-Wave FMCW Radar for Snow Height Measurement: Prototype and Measurements in the 2023-2024 Season - Herráiz-López, Víctor; Subías Martín, Adrián; Salinas, Iñigo; Alonso, Rafael (Jornada de Jóvenes Investigadores del I3A, 2024)
In this paper, we present a prototype of an FMCW radar operating around 120 GHz with a bandwidth of 3.3 GHz, which allows measuring snowpack height with centimeter accuracy. Additionally, we present the results of field measurements conducted during the 2023-2024 winter season at the AEMET-Formigal field laboratory in the Pyrenees.